How not to Understand Community:: A Critical Engagement with R. Bellah - Balogun, Babalola Joseph (Conatus - Journal of Philosophy, 2023)
Robert Bellah’s article “Community Properly Understood…” is critical of the conventional conception of community as a product of consensus established by shared values and goals among people of common social reality. The need for such a critical approach is arguably encouraged by the rather imprecise deployment of the notion of community in the vast communitarian literature, a deployment which truly raises issues of concern over what the term ‘community’ really means. Bellah’s article is one of the numerous responses to this quest. This paper challenges Bellah’s view on community and offers some arguments to demonstrate why his conception of community may not be adequate. While the uniqueness of his argument is not in doubt, the paper argues that Bellah commits a straw man fallacy by conflating a normative question, “what ought we to do to achieve a working and progressive community?” with the descriptive question, “what is community?” The paper argues that an adequate conception of community must be such that its conception is acceptable to both the liberals and the communitarians. To achieve this, the paper introduces the notion of shared spaces to the conceptualization of the concept of community, and thereby arrives at the definition of community in terms with which both sides of the debate can relate. The paper concludes that with an appropriate concept of community, it would be obvious, contrary to the popular opinion, that liberals and communitarians are both committed to the survival of the community, and that they only differ in their respective approaches to achieving this common goal.